Zmierzch czy dostosowanie umowy cywilnoprawnej do warunków ery cyfrowej - Mucha-Kujawa, Joanna (PRAWO i WIĘŹ, 2025)
Contracts have been used for about two and a half thousand years. The structure, functions and objectives of contracts change with the evolution of society and their economy. Currently, in an increasingly digital environment, the contract is also becoming more digital (algorithmized). One of the manifestations of the ongoing changes in contracts is the emergence and intensive development of adhesion contracts, concluded using new technological solutions (smart contracts, contracts created by algorithms) and using the law of other countries. Currently, Contracts no longer have their important self-regulatory and protective function. They do not provide private entities with the independent possibility of regulating their own life matters. They do not fully protect modern consumers against the arbitrary use of the economic power of the stronger party to the contract - entrepreneurs. Furthermore, algorithmized transactions based on smart contracts may in the future lead to the replacement of the classical-positivist model of the contract with a digital model.